Nootkatone Derivative Nootkatone-(E)-2-iodobenzoyl hydrazone Promotes Megakaryocytic Differentiation in Erythroleukemia by Targeting JAK2 and Enhancing JAK2/STAT3 and PKCδ/MAPK Crosstalk - Yang Pan; Feng Xiao; Chaolan Pan; Hui Song; Peng Zhao; Meijun Chen; Liejun Huang; Jue Yang; Xiaojiang Hao (Cells)
Erythroleukemia, a complex myeloproliferative disorder presenting as acute or chronic, is characterized by aberrant proliferation and differentiation of erythroid cells. Although nootkatone, a sesquiterpene derived from grapefruit peel and Alaska yellow cedar, has shown anticancer activity predominantly in solid tumors, its effects in erythroleukemia remain unexplored. This study aimed to investigate the impact of nootkatone and its derivatives on erythroleukemia. Our results demonstrate that the nootkatone derivative nootkatone-(E)-2-iodobenzoyl hydrazone (N2) significantly inhibited erythroleukemia cell proliferation in a concentration- and time-dependent manner. More importantly, N2 induced megakaryocytic differentiation, as evidenced by significant morphological changes, and upregulation of megakaryocytic markers CD41 and CD61. In vivo, N2 treatment led to a marked increase in platelet counts and megakaryocytic cell counts. Mechanistically, N2 activated a crosstalk between the JAK2/STAT3 and PKCδ/MAPK signaling pathways, enhancing transcriptional regulation of key factors like GATA1 and FOS. Network pharmacology and experimental validation confirmed that N2 targeted JAK2, and knockdown of JAK2 abolished N2-induced megakaryocytic differentiation, underscoring JAK2’s critical role in erythroleukemia differentiation. In conclusion, N2 shows great promise as a differentiation therapy for erythroleukemia, offering a novel approach by targeting JAK2-mediated signaling pathways to induce megakaryocytic differentiation.